The Pacific [videorecording (DVD)]. - Dale, James Badge, 1978-; Seda, Jon; Mazzello, Joseph, 1983-; Hanks, Tom (Home Box Office, 2010)
The extraordinary experiences of three men and their fellow Marines take them from the first clash with the Japanese in the haunted jungles of Guadalcanal, through the impenetrable rain forests of Cape Gloucester, across the blasted coral strongholds of Peleliu, up the black sand terraces of Iwo Jima, through the killing fields of Okinawa, to the triumphant, yet uneasy, return home after V-J Day.